A general asymptotic dynamic model for Lipschitzian elastic curved rods - Rostislav Vodák (Journal of Applied Mathematics)
We study the asymptotic behaviour of solutions to the linear evolution problem for clamped curved rods with the small thickness ε under minimal regularity assumptions on the geometry. In addition, nonconstant density of the curved rods is considered.